2002
DOI: 10.1172/jci15528
|View full text |Cite
|
Sign up to set email alerts
|

The role of prostaglandin E2 receptors in the pathogenesis of rheumatoid arthritis

Abstract: Rheumatoid arthritis (RA) is a chronic inflammatory disorder leading to bone and cartilage destruction. A substantial body of evidence suggests that prostaglandin E2 (PGE2) contributes to the pathogenesis of RA, and nonsteroidal anti-inflammatory drugs, inhibitors of the synthesis of PGE2 and other prostanoids, continue to be used in the treatment of this disease. To begin to understand the mechanism by which prostaglandins modulate the pathophysiology of this disease, we examined mice lacking each of the four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
104
1
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 159 publications
(112 citation statements)
references
References 54 publications
4
104
1
3
Order By: Relevance
“…PGE 2 , an important proinflammatory eicosanoid, is involved in the pathogenesis of arthritis (McCoy et al ., 2002). We evaluated the effect of phospho‐aspirin, aspirin, phospho‐sulindac and phospho‐ibuprofen on the production of PGE 2 by NIH 3T3 cells, both under baseline conditions and following stimulation with the calcium ionophore A23187 (Hyman et al ., 1982).…”
Section: Resultsmentioning
confidence: 99%
“…PGE 2 , an important proinflammatory eicosanoid, is involved in the pathogenesis of arthritis (McCoy et al ., 2002). We evaluated the effect of phospho‐aspirin, aspirin, phospho‐sulindac and phospho‐ibuprofen on the production of PGE 2 by NIH 3T3 cells, both under baseline conditions and following stimulation with the calcium ionophore A23187 (Hyman et al ., 1982).…”
Section: Resultsmentioning
confidence: 99%
“…In TLR4 stimulated glomerular mesangial cells, PGE 2 modulated NO production mainly occurred in a cAMP‐dependent manner through the EP 4 receptor (Lin et al ., ). PGE 2 was also found to be capable of controlling the production of IL‐6 via EP 4 in macrophages, in an animal model of rheumatoid arthritis (McCoy et al ., ), and in different cell types. For MCP‐1 it was found that in the process of macrophage migration, activated PGE 2 /EP 4 signalling up‐regulates its expression (Tajima et al ., ).…”
Section: Discussionmentioning
confidence: 98%
“…PGE 2 augments IL-17 production and Th17 differentiation by increasing IL-23 production in T cells and dendritic cells [44,[50][51][52][53], an activity that likely occurs via EP2-and EP4mediated increases in cAMP [54,55]. Additionally, PGE 2 enhances the production of the proinflammatory cytokine IL-6 by leukocytes [56] and airway epithelial cells [57]. PGE 2 potently inhibits the production of a number of antimicrobial peptides (AMPs) such as human β-defensin by epithelial cells [58].…”
Section: Eicosanoids and Immune Functionmentioning
confidence: 99%